Dumb-bell Tumor of The Anterior Chest Wall - Vianna, João B. (2023)
A report is made of a male patient 53 years old presenting a large “dumbbell tumor” of the left side of the anterior chest wall. It had been known by the patient for 6 years but caused no symptoms at all except for its volume. The exact preoperative diagnosis was difficult for even the biopsy disclosed only a fibroma and x-ray examination showed two tumors, one on the outter side and the other on the inner side of the thoraciece wall. A tentative diagnosis of fibroma of the chest wall associated to a cyst of the pericardium was made. During operation the tumor of the mammary region showed a pedicle that extended itself through the 4th left intercostal suace. A thoracotomy was therefore perfomed with resection of part of the anterior wall mesureing 9 ems. x 6 ems. in size and including the 4th and 5th cartilages and ribs. A large dumb-bell tumor was then discovered and removed. The defect on the thoracic wall was closed with fascia lata, pectoralis major and skin. The patient had a normal postoperative course and left the hospital 13 days after the operation. The tumor removed was again studied by the pathologist who came to the conclusion that it was not a simple fibroma but a neurinoma (schwanoma)